ICT-Based Learning in New Normal Era: Viewed from Practice and Impact in ELT Classroom - Hidayah, Jumatul; Prihantoro, Prihantoro (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Covid-19 outbreak has caused a sudden transformation of learning from offline to online modes. Such a transformation raises the importance of ICT as an integral constituent of online learning. Hence, the present mixed-method study aimed to probe into the use of ICT in ELT and the perceived impacts of ICT use on students’ betterment in learning. Eleven English lecturers from the State Islamic Institute of Curup were incorporated as the participants. The quantitative data on the two foci were garnered from a set of an online questionnaires, and the qualitative data were gathered using observations and interviews. This study revealed that the English lecturers used ICT for several pedagogical purposes, such as preparing materials, browsing materials for their lessons, preparing material presentations, and evaluating alongside giving feedback on students' learning. Subsequently, all lecturers perceived that ICT had positive, beneficial, and contributive impacts on students’ betterment in learning especially in terms of enhancing students’ growth mindsets, metacognition, and learning engagement. Further studies are expected to conduct psychometric analyses to examine the interplay among growth mindsets, metacognition, and learning engagement as latent variables within the circle of ICT use in ELT.